2020
DOI: 10.1186/s12944-020-1196-z
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-to-high-density lipoprotein cholesterol ratio is associated with the presence and size of thyroid nodule irrespective of the gender

Abstract: Background: Systemic inflammation may be involved in the formation and progression of thyroid nodule (TN). The aim of this large-scale study was to investigate the association of several simple inflammatory markers with the presence and size of TN. Methods: A total of 133,698 adults were included for the current analysis. The neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), and monocyte-to-high-density lipoprotein cholesterol ratio (MHR) were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Nonetheless rarely has MHR been studied in thyroid disease. One large‐scale study reported that MHR level was significantly increased in patients with thyroid nodules; MHR was significantly associated with the presence of thyroid nodule and strongly associated with the presence and size of thyroid nodule irrespective of gender 34 . There has been no report of a correlation between MHR and PTC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless rarely has MHR been studied in thyroid disease. One large‐scale study reported that MHR level was significantly increased in patients with thyroid nodules; MHR was significantly associated with the presence of thyroid nodule and strongly associated with the presence and size of thyroid nodule irrespective of gender 34 . There has been no report of a correlation between MHR and PTC.…”
Section: Discussionmentioning
confidence: 99%
“…One large‐scale study reported that MHR level was significantly increased in patients with thyroid nodules; MHR was significantly associated with the presence of thyroid nodule and strongly associated with the presence and size of thyroid nodule irrespective of gender. 34 There has been no report of a correlation between MHR and PTC. Our study confirmed our hypothesis that MHR was significantly increased in and closely related to PTC and an independent risk factor for PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular mimicry is considered a possible mechanism underlying the relationship between H. pylori infection and pathophysiology mechanisms of thyroid diseases. In fact, previous evidence has suggested that infection-induced chronic inflammation could be a crucial cause of TN types, which may also be related to the structural similarity between H. pylori epitope antigen and thyroid autoantigen ( Yu et al., 2019 ; Liu et al., 2020 ). It has been reported that 14 proteins of H. pylori antigen epitope are similar to thyroid endogenous proteins, including the segments of human thyrotropin receptor, thyroid autoantigen, and sodium iodide symporter ( Benvenga and Guarneri, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The production of inflammatory cytokines from thyroid-infiltrating mononuclear and follicular cells was associated with Graves disease [18]. Systemic inflammation defined by monocyte-to-high-density-lipoprotein-cholesterol ratio (MHR) might be involved in the development of thyroid nodules (T.N.s) [19]. Leukocytic infiltration mainly constituted by macrophages (inflammation) was normal in transgenic mice expressing RET/PTC3 (RP3, an oncogenic fusion protein in the thyroid gland), with papillary thyroid carcinoma (PTC)-like lesions [20].…”
Section: Introductionmentioning
confidence: 99%